(untitled) (Revista Puertorriqueña de Psicologia, 2016)
In this study we examined the score that a group of outpatient children obtained in the Cuestionario de Personalidad de Niños y Adolescentes. We the compared the scores of this group with a control group of children that were in school. The results revealed that children in treatment obtained higher in the Psychometric Scale, lower scores in the Extraversion Scale and similar scores in the Neuroticism and Lie Scales